2021
DOI: 10.1155/2021/1633231
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Plants from Bangladesh: A Biophytochemical Review and Future Prospect

Abstract: Liver diseases are quite prevalant in many densely populated countries, including Bangladesh. The liver and its hepatocytes are targeted by virus and microbes, as well as by chemical environmental toxicants, causing wide-spread disruption of metabolic fuctions of the human body, leading to death from end-stage liver diseases. The aim of this review is to systematically explore and record the potential of Bangladeshi ethnopharmacological plants to treat liver diseases with focus on their sources, constituents, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 210 publications
0
5
0
Order By: Relevance
“…Numerous studies focusing on plants and their herbal formulations worldwide have reported their hepatoprotective properties. Various phytoconstituents derived from these plants have demonstrated their effectiveness in protecting liver health, both in vitro and in vivo [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies focusing on plants and their herbal formulations worldwide have reported their hepatoprotective properties. Various phytoconstituents derived from these plants have demonstrated their effectiveness in protecting liver health, both in vitro and in vivo [20].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies focusing on plants and their herbal formulations worldwide have reported their hepatoprotective properties. Various phytoconstituents derived from these plants have demonstrated their effectiveness in protecting liver health, both in vitro and in vivo [ 20 ]. For instance, TA, which is abundantly found in cereals, legumes, fruits, herbs, green tea, and red wine, possesses robust antioxidant, astringent, antiviral, and antibacterial properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More than half of pharmaceutical products are from natural compounds and their derivatives [ 9 ]. Around 80% of patients with liver disease use herbal treatments because they are easy to find, have low toxicity, have pharmacological activity and chemical variety, and have common side effects compared to synthetic drugs [ 10 ]. Kaempferol is one of the most common aglycone flavonoids in the form of glycosides.…”
Section: Introductionmentioning
confidence: 99%